Association of insufficient physical activity with sarcopenia and sarcopenic obesity in individuals aged 50 years or more - Santos, Vanessa Ribeiro dos [UNESP]; Castanho Araujo, Monique Yndawe [UNESP]; Cardoso, Michel Rocha [UNESP]; Batista, Vitor Cabrera [UNESP]; Destro Christofaro, Diego Giulliano [UNESP]; Gobbo, Luis Alberto [UNESP] (Pontificia Universidade Catolica Campinas, 2017)
Objective To analyze the association of insufficient physical activity in different domains with sarcopenia or sarcopenic obesity in patients aged >= 50 years. Methods The sample consisted of 770 males and females. Sarcopenia was diagnosed when the individual had: ( 1) low muscle mass and muscle strength; or ( 2) low walking speed and low muscle mass; sarcopenic obesity was diagnosed when individuals were at risk of obesity and sarcopenia. Muscle mass was given by a predictive equation, and then the muscle mass index (in kg/m(2)) was given by muscle mass divided by height squared. Muscle strength, in kg, was given by measuring handgrip strength with a digital dynamometer. The 4m walk test evaluated walking sped. Low muscle mass, muscle strength, and walking speed were defined as the respective values below the 25th percentile, and risk of obesity was defined as body mass index >= 25kg/m(2). Results Habitual physical activity was investigated by a questionnaire. Insufficient leisure-time physical activity was associated with sarcopenia (OR=2.55; 95% CI=1.10-5.88). In addition, insufficient leisure-time physical activity (OR=4.75; 95% CI=1.64-13.72), leisure-time and commuting physical activities (OR=2.49; 95%CI=1.02-6.11, and habitual physical activity (OR=3.55; 95% CI=1.0-11.79) were associated with sarcopenic obesity. Conclusion Insufficient physical activity is associated with sarcopenia or sarcopenic obesity in the study individuals aged >= 50years.
Keywords: Anthropometry; Body composition; Health services; Motor activity; Muscle strength dynamometer